DIVERSITY OF PHYTOPLANKTON IN COASTAL WATER OF KUANTAN, PAHANG, MALAYSIA - Mohammad-Noo, Normawaty; Harun, Siti Nor Rahaida; Mat Lazim, Zainab; Yukinori, Mukai; Mohamad, Najma Tasnim; Saad, Shahbudin (Malaysian Journal of Science, 2013)
A study on diversity of phytoplankton was carried out in the coastal water of Kuantan, Pahang, Malaysia. Eighteen samples of seawater were collected from six stations from September 2011 to March 2012. This study was aimed to identify phytoplankton, to determine the species abundance and diversity. Physico-chemical parameters such as pH, salinity, temperature and dissolved oxygen were recorded. Based on light microscopy, 70 taxa composed of 63 species of diatoms and 7 species of dinoflagellates were identified. Bacteriastrum delicatulum, Chaetoceros spp., and Coscinodiscus spp., were found to be dominant almost at all stations. Some potential harmful species identified were Ceratium fusus, Prorocentrum micans and Chaetoceros sp. The highest cell density was 32 x 103 cells/L and the lowest was 7.9 x 103 cells/L at stations 3 and 5, respectively. Significantly high number of cell density was found during NEM compared to other monsoons. ABSTRAK Satu kajian mengenai kepelbagaian fitoplankton telah dijalankan di sekitar perairan Kuantan, Pahang, Malaysia. Lapan belas sampel air laut telah dikutip di enam stesen dari September 2011 hingga Mac 2012. Kajian ini bertujuan untuk mengenal pasti fitoplankton, menentukan kelimpahan dan kepelbagaian spesies. Fiziko-kimia parameter seperti pH, saliniti, suhu dan oksigen terlarut telah direkodkan. Berdasarkan mikroskop cahaya, 70 taksa yang terdiri daripada 63 spesis diatom dan 7 spesis dinoflagellates telah dikenal pasti. Bacteriastrum delicatulum, Chaetoceros spp., dan Coscinodiscus spp., adalah dominan spesis di hampir semua stesen. Beberapa spesis potensi berbahaya yang dikenal pasti adalah Ceratium fusus, Prorocentrum micans dan Chaetoceros spp. Kepadatan sel tertinggi adalah 32 x 103 sel / L dan yang terendah adalah 7.9 x 103 sel / L di stesen 3 dan 5 masing-masing. Kepadatan sel yang tinggi adalah signifikan pada monson timur laut berbanding dengan monson lain. (Keywords: Phytoplankton, seawater parameter, below surface water, harmful algal bloom, coastal water of Kuantan, light microscopy)